Functional changes in temperature-sensitive mutants of the adenovirus single-stranded DNA-binding protein are accompanied by structural alterations. - Tsuji, M (1992)
Adenovirus requires the virus-encoded single-stranded DNA-binding protein (DBP) to replicate its DNA. We have previously shown (M. Tsuji, P. C. van der Vliet, and G. R. Kitchingman, J. Biol. Chem. 266:16178-16187, 1991) that the inability of three temperature-sensitive (ts) mutant DBPs (Ad2+ ND1ts23, Ad2ts111A, and Ad5ts125) to support DNA replication at the nonpermissive temperature was associated with impaired ability to bind to DNA. In this study, we examined these mutant proteins for structural alterations that might be linked to the functional changes. All three ts mutants, but not the wild-type protein, showed different proteolytic cleavage patterns before and after heating at 40 degrees C (the nonpermissive temperature), suggesting a possible conformational change during heating. The Ad2+ND1ts23 and Ad2ts111A DBPs have single amino acid changes located in a putative zinc finger subdomain (positions 282 and 280). In the presence of zinc ions, these ts mutants showed significantly increased resistance to inactivation at 40 degrees C. Surprisingly, however, the stabilizing effect of zinc was also observed with the Ad5ts125DBP, which contains a mutation located more than 100 amino acids from the zinc finger. Other related metal ions, such as cobalt, cadmium, and mercury, did not protect the ts DBPs from inactivation at 40 degrees C. These results indicate that functional changes of the ts DBPs in DNA replication and DNA binding are accompanied by structural alterations in the protein and that zinc and the metal-binding subdomain may play an important role in the structure and/or function of the DBP.